Rotation schemes of the best female gymnasts in the world - Bessi, F.; Pfeifer, J. (Science of Gymnastics Journal, 2018)
Worldwide trainers ask if there is a rotation scheme, which improves the gymnastics performance and/or facilitates the learning of the elements with longitudinal rotations. Although there are some surveys and scientific publications on it, we still are seeking for more data to understand the undergoing relationships within the rotation habits of high-level gymnasts. In a recent study, the Men`s Individual All Around finalists at the Olympic Games Rio 2016 were categorized using the current classification system of rotational schemes. This study aims first to categorize the Women`s Individual All Around finalists at the Olympic Games Rio 2016. Furthermore; the analysis should help to improve the classification system by comparing both genders. We assume that the female rotation scheme should be more complicated due to the requirements of choreographic movements and gymnastic turns. In this context, the study aims to set a viable classification system for female gymnasts as well. The study revealed that 52% of the female finalists turn to the right while 48% prefer to rotate to the left after having crossedout the dance and gymnastic elements.